Effects of spaceflight aboard the International Space Station on mouse estrous cycle and ovarian gene expression - Xiaoman Hong; Anamika Ratri; Sungshin Y. Choi; Joseph S. Tash; April E. Ronca; Joshua S. Alwood; Lane K. Christenson (npj Microgravity, 2021)
Abstract Ovarian steroids dramatically impact normal homeostatic and metabolic processes of most tissues within the body, including muscle, bone, neural, immune, cardiovascular, and reproductive systems. Determining the effects of spaceflight on the ovary and estrous cycle is, therefore, critical to our understanding of all spaceflight experiments using female mice. Adult female mice (n = 10) were exposed to and sacrificed on-orbit after 37 days of spaceflight in microgravity. Contemporary control (preflight baseline, vivarium, and habitat; n = 10/group) groups were maintained at the Kennedy Space Center, prior to sacrifice and similar tissue collection at the NASA Ames Research Center. Ovarian tissues were collected and processed for RNA and steroid analyses at initial carcass thaw. Vaginal wall tissue collected from twice frozen/thawed carcasses was fixed for estrous cycle stage determinations. The proportion of animals in each phase of the estrous cycle (i.e., proestrus, estrus, metestrus, and diestrus) did not appreciably differ between baseline, vivarium, and flight mice, while habitat control mice exhibited greater numbers in diestrus. Ovarian tissue steroid concentrations indicated no differences in estradiol across groups, while progesterone levels were lower (p < 0.05) in habitat and flight compared to baseline females. Genes involved in ovarian steroidogenic function were not differentially expressed across groups. As ovarian estrogen can dramatically impact multiple non-reproductive tissues, these data support vaginal wall estrous cycle classification of all female mice flown in space. Additionally, since females exposed to long-term spaceflight were observed at different estrous cycle stages, this indicates females are likely undergoing ovarian cyclicity and may yet be fertile.